Conditioning and triggering factors for landslide events in Vitória, Espírito Santo, Brazil - Effgen, Julia Frederica; Marchioro, Eberval (Geografares, 2025)
Every year, Brazil experiences landslides that result in widespread damage, several fatalities and disruption in the daily life of the affected population. In this study, we investigated the main types of landslides in Vitória, their conditioning and triggering factors, and spatial distribution. We compiled a landslide inventory from geological-geotechnical reports and tested the independence and correlation of conditioning and triggering causal factors and landslide events. The most common types of landslides in Vitória are shallow slides and rockfalls, clustered around the Central Massif and coastal hills, where talus deposits, residual soils, and rocky outcrops predominate. The main conditioning factors identified were man-made processes (e.g., defects in drainage systems and modifications in slope geometry) and ground conditions (e.g., weathered materials, contrast in permeability), while the main triggering factors are related to rainfall, especially the high prolonged precipitation events.